(untitled) (Research, Society and Development, 2024)
Objective: Identify humanization techniques used in hospital pediatric care. Methodology: This is an integrative review type of research, which used the following phases: 1. Elaboration of the guiding question; 2. Literature search or sampling; 3. Data collection; 4. Critical analysis of included studies; 5. Discussion of results; 6. Presentation of the review. To this end, the following guiding question was used: What immunization techniques are being used in hospital pediatric care? The selected articles were published between 2015 and 2022 and the databases consulted were: Scielo, MEDLINE (Pubmed Advanced Search) and Lilacs using the descriptors: “Humanization of assistance”, “Hospital Assistance’’, “Pediatrics”, “Child health services”, “Hospitalized child” and “Child care” and their English and Spanish correspondents. Results: Among the 18 finalist articles, six were about therapeutic toys, four were about play therapy, three were about social robots and the rest addressed virtual reality, music therapy and animal-assisted therapy. In addition to reducing levels of anxiety, fear, pain and stress, the use of humanization techniques provides better adaptation and acceptance of the child to the treatment. Conclusion: From this study it is possible to understand the importance of humanization in pediatrics through techniques that enable less traumatic hospitalization and improve care.